2012
DOI: 10.4070/kcj.2012.42.8.538
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic or Anti-Platelet Agents in Patients Undergoing Permanent Pacemaker Implantation

Abstract: Background and ObjectivesThe growing implantations of electrophysiological devices in the context of increasing rates of chronic antithrombotic therapy in cardiovascular disease patients underscore the importance of an effective periprocedural prophylactic strategy for prevention of bleeding complications. We assessed the risk of significant bleeding complications in patients receiving anti-platelet agents or anticoagulants at the time of permanent pacemaker (PPM) implantation.Subjects and MethodsWe reviewed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, it is associated with an increased risk of bleeding with a prevalence of up to 20% for device-pocket hematoma versus 2-4% in patients in whom warfarin was persistently used [17,19,20,25,39]. In some studies, heparin-bridging therapy was reported to pose an even higher risk than DAPT [40]; therefore, the continuation of warfarin therapy during PPI has been favored [39], but this is not possible during TAVR. Continuous multiple anticoagulation therapies are possible, but patients with high HAS-BLED scores or valvular heart disease require careful attention during PPI [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is associated with an increased risk of bleeding with a prevalence of up to 20% for device-pocket hematoma versus 2-4% in patients in whom warfarin was persistently used [17,19,20,25,39]. In some studies, heparin-bridging therapy was reported to pose an even higher risk than DAPT [40]; therefore, the continuation of warfarin therapy during PPI has been favored [39], but this is not possible during TAVR. Continuous multiple anticoagulation therapies are possible, but patients with high HAS-BLED scores or valvular heart disease require careful attention during PPI [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, device-pocket hematoma undoubtedly is an inconvenient complication associated with pain, especially in elderly patients at high risk owing to a prolonged recovery, which leads to pocket infections and wound dehiscence. Furthermore, intraoperative bleeding is related to prolonged procedure time, the increased risk of infection, and prolongation of hospitalization and treatment costs [40].…”
Section: Discussionmentioning
confidence: 99%
“…Close monitoring post-CRT implantation is essential due to potential changes in urine output and electrolyte balance, which may necessitate modifications to the prescribed drugs [110]. Temporarily withdrawing antiplatelet agents before implantation may decrease bleeding risk [111]. Perioperative antibiotic administration has been shown to significantly reduce infection rates [110].…”
Section: Perioperative Periodmentioning
confidence: 99%